2005
DOI: 10.1002/jbm.b.30219
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and treatment of amputation neuroma by an atelocollagen tube in rat sciatic nerves

Abstract: To evaluate the potential of the atelocollagen tube as a cap for amputation neuromas, the histological and histochemical characteristics of the neuroma and spinal cord were compared with those following silicone capping. Four weeks after the transection of 18 rat sciatic nerves, the amputated neuroma was resected, and the nerve stump inserted into an atelocollagen or silicone tube. The histological changes in the nerve ends and c-fos expression in the dorsal horn of the fourth lumbar spinal cord were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 22 publications
1
34
0
Order By: Relevance
“…However, no studies have yet to convincingly confirm whether or not the observed behavior is directly related to pain [15]. Although quantitative assessment of tactile allodynia [37] or thermal hyperalgesia [38] in the rat paw is a simple method to assess the neuropathic pain in the current study, the presence of autotomy precludes this approach.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…However, no studies have yet to convincingly confirm whether or not the observed behavior is directly related to pain [15]. Although quantitative assessment of tactile allodynia [37] or thermal hyperalgesia [38] in the rat paw is a simple method to assess the neuropathic pain in the current study, the presence of autotomy precludes this approach.…”
Section: Discussionmentioning
confidence: 86%
“…Although quantitative assessment of tactile allodynia [37] or thermal hyperalgesia [38] in the rat paw is a simple method to assess the neuropathic pain in the current study, the presence of autotomy precludes this approach. Therefore, the common pain-related markers, c-fos [15], [39] and substance P [40], [41], were then selected to evaluate the pain status of the neuromas. Our findings in this study showed that the expression of c-fos in the dorsal horn of L4 spinal cord was significantly decreased in the capping group compared to the no-capping group both at 2 weeks and 8 weeks after neurectomy; on the other hand, the substance P release was also inhibited in the neuromas of the capping group when compared with that of the no-capping group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, various laser methods were proved to be effective in such prevention of neuroma development 19. Nerve fibers outgrow can be also hindered pharmacologically,20 by systemic application of melatonin,21 or local application of atelocollagen or alginate around sectioned nerve 22. Other methods, like epineural flap technique to cap the proximal nerve stump, are seldom but still used in the surgical practice 16.…”
Section: Discussionmentioning
confidence: 99%
“…New methods and techniques in nerve surgery such as collagen nerve guides and tubes are being studied for the treatment of painful neuromas [15,16]. Up to now these techniques have been applied in animal experiments with encouraging results but as yet no clinical work has been published.…”
Section: Discussionmentioning
confidence: 99%